2018
DOI: 10.1016/j.jhealeco.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Price competition in pharmaceuticals – Evidence from 1303 Swedish markets

Abstract: We study the short- and long-term price effects of the number of competing firms, using panel-data on 1303 distinct pharmaceutical markets for 78 months within a reference-price system. We use actual transaction prices in an institutional setting with little scope for non-price competition and where simultaneity problems can be addressed effectively. In the long term, the price of generics is found to decrease by 81% when the number of firms selling generics with the same strength, form and similar package siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 38 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…This suggests that the price of a generic drug is inversely related to the number of labelers of the drug that had ever been approved 3–9 years earlier. This finding is consistent with the evidence surveyed and developed by Granlund and Bergman (2018). Estimates of β 3 have the largest magnitudes.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…This suggests that the price of a generic drug is inversely related to the number of labelers of the drug that had ever been approved 3–9 years earlier. This finding is consistent with the evidence surveyed and developed by Granlund and Bergman (2018). Estimates of β 3 have the largest magnitudes.…”
Section: Resultssupporting
confidence: 94%
“…There have been numerous econometric studies of the effect of within‐substance competition on drug prices. See Granlund and Bergman (2018) for a brief summary of the findings of about a dozen of those studies and for new evidence about Sweden. Most of those studies found that an increase in the number of generic suppliers of a drug substantially reduced the average price of generic versions of it, especially in the US Evidence about the effect of generic entry on the price of the branded product is somewhat mixed 5 .…”
Section: Introductionmentioning
confidence: 99%
“…This paper relates to Bergman et al (2017) and Granlund and Bergman (2018)both of which used dynamic models to study competition effects. However, these papers studied prices for off-patent pharmaceuticals and focused on the effects of competition from generic substitutes.…”
Section: Introductionmentioning
confidence: 99%
“…Patent expiries and the subsequent introduction of generics have a big impact on drug prices in Sweden with the main effects normally observed after a few months following launch of the generic alternatives [28]. Therefore, the precision of our estimate of the timing when generics become available to a large degree affects the accuracy of our forecast.…”
Section: Discussionmentioning
confidence: 99%